Paralytic effect of fasciolicidal agents on rhythmic motility of Fasciola gigantica - Kumar, D; Tripathi, H C (The Indian Journal of Animal Sciences, 2012)
Effect of some clinically used fasciolicides was assessed on the rhythmic motility of Fasciola gigantica to evaluate their possible action on the neuromuscular system of the fluke. The mature flukes collected from the local abattoir were either mounted isometrically or incubated in Hedon-Fleig solution. Hexachlorophene (10-6 M), niclofolan (10-5 M) and oxyclozanide (10-6 M) induced rapid, persistent and tonic paralysis of the flukes. However, rafoxanide (3 x 10-4 M) caused slow, partial and flaccid paralysis of the fluke. Albendazole and triclabendazole did not show any paralytic effect on fluke rhythmicity. The gross visual motility was inhibited completely within half an hour of incubation and the flukes were paralyzed in tonic state by hexachlorophene ( 10-5 M), niclofolan ( 10-5 M) and oxyclozanide (10-5 M), while the same was inhibited slowly by rafoxanide, albendazole and triclabendazole. It is concluded from the results that hexachlorophene, niclofolan and oxyclozanide produced their fasciolicidal effect by affecting neuromuscular system of the fluke whereas rafoxanide, albendazole and triclabendazole may have effect on energy metabolism and or may be affecting the tegument of the fluke. The results may facilitate developing combination therapy against F. gigantica.